OPTIMALISASI PELAYANAN UNIT PENYELENGGARA BANDARA UDARA PADA SAAT PENDEMI COVID 19 DI BANDAR UDARA KOMODO LABUAN BAJO - Selmawati; Awan,S.SiT.(Pnb).,M.M (Pusat Riset dan Inovasi Nasional, 2023)
Komodo Labuan bajo Airport is one of the companies that offers services in the field of aviation that will use air transportation services,.Before boarding the avsec officer will check the completeness of the trip before entering the area within the airport (check in ).in handling the avsec officer,of course there are several things which is an advantage for the company and Avsec officers,such as in terms of service,for service users so that the output obtained by the company will also be better.knowing the obstacles faced in the service of the airport operator unit during the pandemic. The study use a qualitative method.the data sources used are primary data and secondary data.the method or documentation technique used in this study is to obtain interview and observation data based on the results of research that has been carried out.The results of the study show that (1) the optimization of the Airport Operator unit service includes ensuring that passengers meet flight requirements during the covid 19 pandemic.(2) The problem is that many Avsec officers do not comply with health protocols such as crowding,not wearing masks,not keeping their distance,even playing with cellphones while checking passengers,and it happened that one of the passenggers did not meet one flight requirement.however,it is allowed to enter or travel.